The Role of Female Teachers in Encouraging Women's Empowerment in Schools - Rahmaditha, Khairani; Virmanedi Putra, Gilang; Desvi Yolanda, Dilla; Hudia, Tasya; Milla Quaidy, Gusti (HUMANISMA : Journal of Gender Studies, 2024)
This research explores the strategic role of female teachers in encouraging female students to take leadership roles and participate actively in school. Although female students often face barriers such as gender stereotypes, social pressure, and lack of support, female teachers have the potential to overcome these challenges through a variety of strategies. This study highlights how female teachers can be inspirational role models, create inclusive learning environments, and provide positive and constructive feedback. In addition, through the integration of gender equality education in the curriculum, class discussions, seminars, mentoring programs, and the provision of educational resources, female teachers can increase female students' awareness and understanding of their rights and the importance of gender equality. The research method used in this research is library research with an approach that involves collecting and analysing information from various existing written sources. The results showed that support and guidance from female teachers not only increased female students' self-confidence and motivation but also equipped them with leadership skills that are important for future success. Thus, this research emphasises the important role of female teachers in empowering women in the educational environment, as well as their contribution to creating a more just and equal society.